1998
DOI: 10.1136/oem.55.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and physical risk factors associated with low back pain: a 24 year follow up among women and men in a broad range of occupations.

Abstract: Both psychosocial factors and physical factors related to work have been found to be associated with low back pain (LBP) in many cross sectional and some longitudinal studies. [1][2][3][4] In analyses of potential risk factors for LBP related to work, often physical factors only, or psychosocial factors only, have been considered. Less often both types of factors have been studied and analysed simultaneously. 5 Even less often have conditions outside work been studied in parallel with work related conditions.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2
8

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 18 publications
3
46
2
8
Order By: Relevance
“…The increase in prevalence of low back pain as years of farming increase may be due to accumulation of repetitive strain of the muscles and ligaments of the back consequent to inconvenient posture assumed during farm activities. The high prevalence of low back pain among male farmers may be due to the fact that they are more involved in heavy manual physical activities than their female counterparts [28,29]. However, this finding disagrees with those of previous studies which concluded that LBP was more frequent among females [28,29].…”
Section: Discussioncontrasting
confidence: 57%
“…The increase in prevalence of low back pain as years of farming increase may be due to accumulation of repetitive strain of the muscles and ligaments of the back consequent to inconvenient posture assumed during farm activities. The high prevalence of low back pain among male farmers may be due to the fact that they are more involved in heavy manual physical activities than their female counterparts [28,29]. However, this finding disagrees with those of previous studies which concluded that LBP was more frequent among females [28,29].…”
Section: Discussioncontrasting
confidence: 57%
“…The few long-term population-based studies available have focused on groups with back pain and not on the group without back disorders [7,9,16].…”
Section: T Reigo H Tropp T Timpkamentioning
confidence: 99%
“…In this study, the prevalence of LBP was 24% among men and 34% among women in 1969, and the cumulative incidence of LBP from 1970 to 1992 were 43% and 38% among men and women, respectively. The prevalence of LBP over the past 12 months in 1993 was 39% among men and 44% among women (Thorbjornsson et al, 1998). Moreover, the highest associations between work related factors and LBP (prevalence ratio adjusted for age) was high physical load (1.4) among men and monotonous work (1.6) among women in 1969, full time work (2.1) among men and high mental load (1.4) among women in 1970-1992, and monotonous work (1.5) among men and poor social support (1.2) among women in 1993, respectively (Thorbjornsson et al, 1998).…”
Section: Risk Factors Of Occupational Lbpmentioning
confidence: 99%
“…Risk estimates of manual material handling, frequent bending and twisting, heavy physical load, static work posture, repetitive movements, and whole-body vibrations for positive associations in physical risk factors at work ranged from 1.12 to 3.07, from 1.29 to 8.09, from 1.54 to 3.71, from 1.30 to 3.29, 1.97, and from 1.47 to 9.00, respectively, and risk estimates of mental stress, job dissatisfaction, work pace, and monotonous work for positive associations in psychological risk factors at work ranged from 1.30 to 2.08, from 1.39 to 2.40, 1.21, and from 1.25 to 2.34, respectively (Burdorf & Sorock, 1997). Thorbjornsson et al, investigated the psychosocial and physical risk factors associated with LBP for over 24 years from 1969 to 1993 (Thorbjornsson et al, 1998). In this study, the prevalence of LBP was 24% among men and 34% among women in 1969, and the cumulative incidence of LBP from 1970 to 1992 were 43% and 38% among men and women, respectively.…”
Section: Risk Factors Of Occupational Lbpmentioning
confidence: 99%